2007
DOI: 10.1152/ajpregu.00254.2006
|View full text |Cite
|
Sign up to set email alerts
|

Novel axonal projection from the caudal end of the ventrolateral medulla to the intermediolateral cell column

Abstract: We used an optical imaging technique to investigate whether axons of neurons in the caudal end of the ventrolateral medulla (CeVLM), as well as axons of neurons in the rostral ventrolateral medulla (RVLM), project to neurons in the intermediolateral cell column (IML) of the spinal cord. Brain stem-spinal cord preparations from neonatal normotensive Wistar-Kyoto and spontaneously hypertensive rats were stained with a voltage-sensitive dye, and responses to electrical stimulation of the IML at the Th2 level were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Thus, in the present study, we investigated the effect of aldosterone, eplerenone (an MR blocker), FAD286 (an aldosterone synthase inhibitor) and benzamil (an epithelial sodium channel (ENaC) blocker) on bulbospinal RVLM neurons using brainstem-spinal cord preparations that preserved the sympathetic nervous system. [11][12][13][14][15][16][17][18][19][20] As a previous report showed that intracerebroventricular infusion of eplerenone lowered blood pressure, 2, 21 we examined the direct effect of eplerenone on RVLM neurons, using a low-Ca 2 þ , high-Mg 2 þ solution to block synaptic input into RVLM neurons. Aldosterone performs its function in the collecting ducts of the kidneys, and ENaCs are known to participate in the process through genomic action.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in the present study, we investigated the effect of aldosterone, eplerenone (an MR blocker), FAD286 (an aldosterone synthase inhibitor) and benzamil (an epithelial sodium channel (ENaC) blocker) on bulbospinal RVLM neurons using brainstem-spinal cord preparations that preserved the sympathetic nervous system. [11][12][13][14][15][16][17][18][19][20] As a previous report showed that intracerebroventricular infusion of eplerenone lowered blood pressure, 2, 21 we examined the direct effect of eplerenone on RVLM neurons, using a low-Ca 2 þ , high-Mg 2 þ solution to block synaptic input into RVLM neurons. Aldosterone performs its function in the collecting ducts of the kidneys, and ENaCs are known to participate in the process through genomic action.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14]17,18 The protocols of the experiments were approved by the Institutional Review Board of Keio University School of Medicine, Tokyo, and were in accord with the National Guidelines for the Conduct of Animal Experiments. With the animals under deep ether anesthesia, the brainstem-spinal cord was isolated together with other organs (including the heart, carotid sinuses and aorta), which were maintained intact ( Figure 1).…”
Section: General Preparationsmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14] In an earlier study, 9 we performed whole-cell recordings of rostral ventrolateral medulla (RVLM) neurons and classified them into three types according to their discharge patterns. We have also demonstrated monosynaptic connections between neurons in the RVLM and sympathetic pre-ganglionic neurons by simultaneous recording using the same preparation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17][18][19][20][21][22] While recording the membrane potentials (MPs) of the bulbospinal RVLM neurons using the patch-clamp technique, the neurons were superfused with metoprolol (b 1 -AR antagonist), dobutamine (b 1 -AR agonist), butoxamine (b 2 -AR antagonist) or salbutamol (b 2 -AR agonist). Furthermore, to examine the direct effects of metoprolol or butoxamine on the RVLM neurons, the superfusion was conducted with each drug dissolved in a low-Ca 2 þ , high-Mg 2 þ or tetrodotoxin (TTX) solution.…”
Section: Introductionmentioning
confidence: 99%